Method to map antigenic determinants recognized by monoclonal antibodies: localization of a determinant of virus neutralization on the feline leukemia virus envelope protein gp70. - Nunberg, J H (1984)
A method is presented whereby antigenic determinants recognized by specific monoclonal antibodies can be mapped to specific sites on a protein sequence with high resolution. Short DNase I-generated DNA fragments encoding portions of the protein of interest are molecularly cloned into the EcoRI site of the beta-galactosidase gene of phage lambda Charon 16 so as to obtain expression of random protein fragments as fusion proteins. The monoclonal antibody is used to screen the phage library to isolate phage expressing the specific antigenic determinant. DNA of immunoreactive phage can be analyzed rapidly and subcloned to allow DNA sequence determination. The method is generally applicable and permits antigenic determinants of functionally interesting monoclonal antibodies to be mapped and related to specific protein sequences. We have used this procedure to determine the region of the feline leukemia virus envelope protein gp70 recognized by a virus-neutralizing monoclonal antibody, cl.25. Antibody binding was mapped to a 14-amino acid region in the amino-terminal half of gp70. This region may be directly involved in an essential function of the gp70 protein, perhaps in gp70-mediated host recognition functions. Synthetic peptides derived from this region may provide useful vaccine antigens for the prevention of feline leukemia virus-associated disease in cats.